2010
DOI: 10.1105/tpc.110.080283
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisFIMBRIN5, an Actin Bundling Factor, Is Required for Pollen Germination and Pollen Tube Growth

Abstract: Actin cables in pollen tubes serve as molecular tracks for cytoplasmic streaming and organelle movement and are formed by actin bundling factors like villins and fimbrins. However, the precise mechanisms by which actin cables are generated and maintained remain largely unknown. Fimbrins comprise a family of five members in Arabidopsis thaliana. Here, we characterized a fimbrin isoform, Arabidopsis FIMBRIN5 (FIM5). Our results show that FIM5 is required for the organization of actin cytoskeleton in pollen grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
111
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 65 publications
8
111
0
Order By: Relevance
“…Our experiments using cross-linked proteins and native gels demonstrated that CROLIN1 forms oligomers to bundle and cross-link F-actin. Moreover, the actin structure induced by CROLIN1 in vitro was similar to that of FIM1 and FIM5, which form higher order actin structures (12,13). These results reveal that the mechanism of actin bundling by CROLIN1 is different from the mechanism of other ABPs, such as formin (16) and villin (7), which mainly form actin cables and bundles.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Our experiments using cross-linked proteins and native gels demonstrated that CROLIN1 forms oligomers to bundle and cross-link F-actin. Moreover, the actin structure induced by CROLIN1 in vitro was similar to that of FIM1 and FIM5, which form higher order actin structures (12,13). These results reveal that the mechanism of actin bundling by CROLIN1 is different from the mechanism of other ABPs, such as formin (16) and villin (7), which mainly form actin cables and bundles.…”
Section: Discussionmentioning
confidence: 57%
“…For example, a VLN5 loss-of-function mutant displays delayed pollen tube growth and results in F-actin in both pollen grains and pollen tubes that are sensitive to latrunculin B (Lat B) (7). A loss-of-function mutant of Arabidopsis FIMBRIN5 also results in delayed pollen germination and inhibited tube growth, with both pollen germination and tube growth being hypersensitive to Lat B (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The quantity and binding ratio of RIC1 and actin were measured using ImageJ software. The equilibrium K d value was determined as described by Wu et al (2010). RIC1 in the pellet ([RIC1] bound ) was plotted as a function of RIC1 in the supernatant ([RIC1] free ), and the data were fitted with a hyperbolic function using Kaleidagraph version 4.0 software (Synergy Software).…”
Section: Cosedimentation Assaysmentioning
confidence: 99%
“…Several classes of actin bundlers have been characterized in plants, including villins (7)(8)(9)(10)(11)(12), fimbrins (13,14), certain formins (15,16), and LIM proteins (17)(18)(19). These actin bundlers are also present in most other eukaryotes.…”
mentioning
confidence: 99%